Knockdown of mitochondrial alternative oxidase induces the 'stress state' of signaling molecule pools in Nicotiana tabacum, with implications for stomatal function. Issue 2 (18th March 2014) - Cvetkovska, Marina; Dahal, Keshav; Alber, Nicole A.; Jin, Cathy; Cheung, Melissa; Vanlerberghe, Greg C.
Summary The mitochondrial electron transport chain (ETC) includes an alternative oxidase (AOX) that may control the generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS). ROS and RNS act as signaling intermediates in numerous plant processes, including stomatal movement. The role of AOX in controlling ROS and RNS concentrations under both steady‐state and different stress conditions was evaluated using Nicotiana tabacum plants lacking AOX as a result of RNA interference. A potential functional implication of changes in ROS and RNS homeostasis was also evaluated by examining stomatal function. The leaves of nonstressed AOX knockdowns maintained concentrations of H2O2 and nitric oxide (NO) normally seen in wildtype plants only under stress conditions. Further, guard cell NO amounts were much higher in knockdowns. These guard cells were altered in size and were less responsive to NO as a signal for stomatal closure. This, in turn, compromised the stomatal response to changing irradiance. The results reveal a role for AOX in stomata. A working model is that guard cell AOX respiration maintains NO homeostasis by preventing over‐reduction of the ETC, particularly during periods when high concentrations of NO acting as a signal for stomatal closure may also be inhibiting cyt oxidase respiration.